2011
DOI: 10.1039/c1sm05555k
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origin of the terminal relaxation time in polymer nanocomposites: an experimental precedent

Abstract: By means of rheology and neutron spin echo spectroscopy, both a macroscopic and a microscopic view on the relaxation dynamics of polymers in the presence of non-attractive nanoparticles could be realized. The results enabled us to show a direct correlation between the microscopically observed confinement length and the macroscopically measured dissipation maximum, which corresponds to the terminal relaxation time. Moreover, the impact of nanoparticle presence on the effectiveness of polymer contour length fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…For the polymer melts interacting with a confining surface, they found an anchored surface layer with internal high mobility, which was considered to be glassy in past works [370,376]. In addition, for poly(ethylene-alt-propylene) (PEP) matrices filled with hydrophobic (non-attractive) silica NPs, they reported several key findings [374,375]: (i) the Gaussian behavior of polymer chains was still preserved at a high volume fraction of NPs; (ii) NPs were found to have negligible influence on the basic Rouse relaxation rate of PEP chains; (iii) the effective lateral confining length of PEP chains increased with the NP volume fraction; (iv) a crossover from polymer chain entanglements to "NP entanglements" was observed with a critical NP volume fraction of about 35%; and (v) both the CLF and CR effects were suppressed by the appearance of NPs. All of these key findings, except (ii) and (v), were later observed by Li et al [329] in large-scale isobaric MD simulations with generic NPs.…”
Section: Polymer Dynamics At Interfaces and In Interphasesmentioning
confidence: 90%
See 2 more Smart Citations
“…For the polymer melts interacting with a confining surface, they found an anchored surface layer with internal high mobility, which was considered to be glassy in past works [370,376]. In addition, for poly(ethylene-alt-propylene) (PEP) matrices filled with hydrophobic (non-attractive) silica NPs, they reported several key findings [374,375]: (i) the Gaussian behavior of polymer chains was still preserved at a high volume fraction of NPs; (ii) NPs were found to have negligible influence on the basic Rouse relaxation rate of PEP chains; (iii) the effective lateral confining length of PEP chains increased with the NP volume fraction; (iv) a crossover from polymer chain entanglements to "NP entanglements" was observed with a critical NP volume fraction of about 35%; and (v) both the CLF and CR effects were suppressed by the appearance of NPs. All of these key findings, except (ii) and (v), were later observed by Li et al [329] in large-scale isobaric MD simulations with generic NPs.…”
Section: Polymer Dynamics At Interfaces and In Interphasesmentioning
confidence: 90%
“…For this reason, many computational and experimental works have been performed in recent years to understand the polymer dynamics at the interface and in the interphase [127,128,328,329,[370][371][372][373][374][375][376][377][378][379][380][381][382]. While extensive works have been done to explore the chain dynamics inside PNCs, widely different and often conflicting results are reported.…”
Section: Polymer Dynamics At Interfaces and In Interphasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a particular slowing down of long-wavelength Rouse modes cannot be excluded, since the signature of such Rouse modes would be overshadowed by confinement effects. In a following article 43 it is also shown that the extracted confinement length can be directly connected with rheological data from the same samples. In addition, qualitative evidences were also found from the rheological data that the contour length fluctuations and constraint release mechanisms are less effective in nanocomposites with high concentration of NPs.…”
Section: Nanocomposites Solid Polyelectrolytes and Blendsmentioning
confidence: 99%
“…Semicrystalline polymers, 37,38 solid polyelectrolytes, [39][40][41] nanocomposites 39,[42][43][44] and polymer blends 45 have been subject of QENS studies by several groups. In many of those works, confinement effects arise as a key ingredient.…”
Section: Recent Progress On Polymer Dynamics By Neutron Scatteringmentioning
confidence: 99%